INFERTILITY, THEIR OCCURRENCE AND SPECIFIC ANOMALIES OF ORGANISMS - Otajonova Dilfuza Otabek Qizi (Scholar Express Journals, 2021)
Reproduction is required for the survival of all mammalian species, and thousands of essential ‘sex’ genes are conserved through evolution. Basic research helps to define these genes and the mechanisms responsible for the development, function and regulation of the male and female reproductive systems. However, many infertile couples continue to be labeled with the diagnosis of idiopathic infertility or given descriptive diagnoses that do not provide a cause for their defect. For other individuals with a known etiology, effective cures are lacking, although their infertility is often bypassed with assisted reproductive technologies (ART), some accompanied by safety or ethical concerns. Certainly, progress in the field of reproduction has been realized in the twenty-first century with advances in the understanding of the regulation of fertility, with the production of over 400 mutant mouse models with a reproductive phenotype and with the promise of regenerative gonadal stem cells. Indeed, the past six years have witnessed a virtual explosion in the identification of gene mutations or polymorphisms that cause or are linked to human infertility. Translation of these findings to the clinic remains slow, however, as do new methods to diagnose and treat infertile couples. Additionally, new approaches to contraception remain elusive. Nevertheless, the basic and clinical advances in the understanding of the molecular controls of reproduction are impressive and will ultimately improve patient care
Keywords: Genital tracts; embryo; Fertility; Infertility